Transmitted Cross-Polarized Light Detection of Particulate Inorganic Carbon Concentrations and Fluxes in the Ocean Water Column: Ships to ARGO Floats - Bishop, James K. B.; Amaral, Vinicius J.; Lam, Phoebe J.; Wood, Todd J.; Lee, Jong-Mi; Laubach, Allison; Barnard, Andrew; Derr, Alex; Orrico, Cristina (Frontiers in Remote Sensing, 2022)
Particulate inorganic carbon (PIC) plays a major role in the ocean carbon cycle impacting pH, dissolved inorganic carbon, and alkalinity as well as particulate organic carbon (POC) export and transfer efficiency to the deep sea. Remote sensing retrievals of PIC in surface waters span two decades, yet knowledge of PIC concentration variability in the water column is temporally and spatially limited due to a reliance on ship sampling. To overcome the space- time gap in observations we have developed optical sensors for PIC concentration and flux that exploit the high mineral birefringence of CaCO3 minerals and thus enable real time data when deployed operationally from ship CTDs, and ARGO- style Carbon Flux Explorer floats. For PIC concentrations, we describe a fast (10Hz) digital low-power (~0.5W) sensor that utilizes cross-polarized transmitted light to detect the photon yield from suspended birefringent particles in the water column. This sensor has been CTD- deployed to depths as great as 6000 m – and cross calibrated against particulates sampled by large volume in- situ filtration and CTD/rosettes. We report data from the Sept. – Nov. 2018 GEOTRACES GP15 meridional transect from the Aleutian Islands to Tahiti along 152°W where we validated two prototype sensors deployed on separate CTDs surface to bottom at 39 stations, many of which were taken in nearly particle free waters. We compare sensor results with major particle phase composition (particularly PIC and particulate aluminum) from simultaneously collected size- fractionated particulate samples collected by large volume in- situ filtration. We also report results from the June 2017 California Current Ecosystem-Long Term Ecological Research (CCE-LTER) process study in California coastal waters where high PIC levels were found. We demonstrate that the PIC concentration sensor can detect PIC concentration variability from 0.01 μM to >1 μM in the water column (except in nepheloid layers) and outline engineering needs and progress on its integration with the Carbon Flux Explorer, an autonomous float.